Avian Hepatitis E Virus: With the Trend of Genotypes and Host Expansion - Sun, Peng; Lin, Shaoli; He, Shenghu; Zhou, En-Min; Zhao, Qin (Frontiers in Microbiology, 2019)
Avian hepatitis E virus (HEV) is a single-stranded, positive-sense RNA virus with a complete genome of approximately 6.6 kb in size. To date, four major genotypes of avian HEV have been identified and classified into the Orthohepevirus B genus of the family Hepeviridae. The avian HEV associated with hepatitis-splenomegaly syndrome, big liver and spleen disease or hepatic rupture hemorrhage syndrome in chickens is genetically and antigenically related to mammalian HEV. With the increased genotypes of avian HEV identified, a broader host tropism is also notable in the epidemiological studies. Due to the lack of an efficient cell culture system, the mechanisms of avian HEV replication and pathogenesis are still poorly understood. The recent identification and characterization of animal strains of avian HEV has demonstrated the virus’ ability of cross-species infection. Although it has not yet been detected in humans, the potential threat of a zoonotic HEV capable of transmission to humans needs to be taken into consideration. This review article focuses on the current knowledge regarding avian HEV in virology, epidemiology, pathogenesis, clinical presentation, transmission, diagnosis and prevention. HIGHLIGHTS - The mechanisms of avian HEV replication and pathogenesis are still poorly understood due to the lack of an efficient cell culture system. - A broader host tropism is also notable in the epidemiological studies with the increased genotypes of avian HEV identified. - The recent identification and characterization of animal strains of avian HEV has demonstrated the virus’ ability of cross-species infection. - The potential threat of a zoonotic HEV capable of transmission to humans needs to be taken into consideration.